2023
DOI: 10.3390/pr11051445
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Mechanisms of Laser Cleaning Technology and Its Typical Applications in Industry

Abstract: Laser cleaning is an advanced surface-cleaning technology that can lead to the instant evaporation and stripping of the attachments found on a substrate’s surface, such as contaminants, rust, and coatings; it uses a high-energy laser beam to irradiate the components’ surface. Compared with common surface-cleaning technologies, laser cleaning has the advantages of precision, efficiency, and controllability. In this paper, the fundamental mechanisms of laser cleaning technology are summarized in detail; these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition, Nishihara et al (2019) cleaning of molds is performed using a 70W fiber laser to remove dirt and oil from metal surfaces. Zhihu Zhou et al (2023) have also explained the mechanism of laser cleaning and confirmed its effectiveness for cleaning metal and non-metal materials. Matsui (2003) reported the superiority of using lasers for graffiti removal on concrete.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, Nishihara et al (2019) cleaning of molds is performed using a 70W fiber laser to remove dirt and oil from metal surfaces. Zhihu Zhou et al (2023) have also explained the mechanism of laser cleaning and confirmed its effectiveness for cleaning metal and non-metal materials. Matsui (2003) reported the superiority of using lasers for graffiti removal on concrete.…”
Section: Introductionmentioning
confidence: 89%
“…Lasers have quickly expanded in several industries because of their superior and remarkable qualities. Currently, practically every industry, including national defence, agriculture, and manufacturing, uses lasers extensively (Ion, 2005;Tong et al, 2022;Zhou et al, 2023). High-power laser sources offer new opportunities for material processing with different wavelengths.…”
Section: Figure 2 Basic Principles Of Laser Beam Generation (Justande...mentioning
confidence: 99%
“…The substance usually turns into plasma at high laser flux levels. Additionally, the covalent bonds in the polymer chains are broken by the energy of the UV photons, which causes photochemical ablation [15]. Corneal ablation using ultraviolet (UV) short pulsed lasers doesn't rise the temperature of the eye to significant values [16].…”
Section: Introductionmentioning
confidence: 99%